The Effectiveness of the Communication Style of Health Cadres Through Local Culture on Awareness of Stunting - Yogi Friando; Manik Sunuantari (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2025)
Stunting continues to pose a significant public health challenge in Indonesia, particularly in the Kebon Kacang Subdistrict of Central Jakarta. This research is purposed to measure the effectiveness of communication style of health cadres through local culture on awareness of stunting among mothers. The study used a quantitative method of 50 respondents through accidental sampling. The theoretical framework comprised the Communicator Style Theory (Norton), Local Culture (Koentjaraningrat), and the Health Belief Model (Rosenstock). The correlation and linear regression analyses demonstrate that the communication style of health cadres significantly impacts stunting awareness (β = 0.702), while local culture also exhibits a positive correlation with stunting awareness (r = 0.628, p < .001). The coefficient of determination indicatess that the model accounts for the dependent variable effectively, as reflected by an R Square value of 0.752. These findings indicate that communication style through local culture can enhance mother’s understanding and awareness in efforts to prevent stunting more effectively.